EVOLUTION OF LARGE-SCALE VARIATIONS OF LOWER-THERMOSPHERIC PARAMETERS OVER IRKUTSK - Kokourov V.D.; Kazimirovsky E.S.; Vergasova G.V. (My University, 2006)
For the first time, using many years of measurements of lower-thermospheric parameters (the horizontal wind velocity for 1976-1995, and minimum reflection frequency for 1983-1991) over Irkutsk (52°N, 105°E), the dynamics of their large-scale variations was investigated. The study used a sliding multiple correlation periodogram analysis. Regular seasonal, semi-annual and annual variations were detected. Quasi-biennial variations are regarded as irregular variations with a constantly changing over a rather wide range period. Variations with similar periods were also detected in the planetary index of geomagnetic activity Ap, and in the solar radio flux index F10.7. Our correlation analysis indicates that large-scale variations of the wind velocity and fmin in the lower thermosphere are correlated with those in the geomagnetic field. The large-scale variations under investigation characterize a regular long-term variability of lower-thermospheric parameters and can serve as climatic characteristics for the description of the climate of this atmospheric region. © 2006 Elsevier Ltd. All rights reserved.
Keywords: LOWER THERMOSPHERE; REGULAR VARIATIONS; SIBERIA